Clinical reasoning in anaphylactic shock: addressing the challenges faced by anaesthesiologists in real time. Issue 11 (November 2021) - Gouel-Cheron, Aurelie; Neukirch, Catherine; Kantor, Elie; Malinovsky, Jean-Marc; Tacquard, Charles; Montravers, Philippe; Mertes, Paul-Michel; Longrois, Dan
Abstract : N/A: Acute hypersensitivity reactions to drugs occur infrequently during anaesthesia and the peri-operative period. When clinical presentation includes the classical triad, erythema, cardiovascular abnormalities and increased airway pressure, the diagnosis is evident and the challenge is to prescribe a therapeutic regimen according to guidelines and to manage refractory signs in a timely manner. In many situations, however, the initial clinical signs are isolated, such as increased airway pressure or arterial hypotension. Rendering a differential diagnosis with causes and mechanisms other than acute hypersensitivity reactions (AHRs) is difficult, delaying treatment with possible worsening of the clinical signs, and even death, in previously healthy individuals. In these difficult diagnostic situations, clinical reasoning is mandatory, and guidelines do not explicitly explain the elements on which clinical reasoning can be built. In this article, based on clinical evidence whenever available, experimental data and pathophysiology, we propose algorithms that have been evaluated by experts. The goal of these algorithms is to provide explicit elements on which the differential diagnosis of AHRs can be made, accelerating the implementation of adequate therapy.